Intellectual Capital, Islamic Philanthropy, and Sustainability Development Goals: An Interpretive Management Accounting Research - Sigit Hermawan; Sarwenda Biduri; Sintha Wahyu Arista; Prasetyo Utomo (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2025)
This study aims to examine the role of Intellectual Capital (IC) in improving the performance of Islamic philanthropic institutions (amil zakat) in Indonesia in order to achieve the Sustainable Development Goals (SDGs). The research method chosen is qualitative with the Interpretive Management Accounting Research (IMAR) approach conducted with 26 key informants, including institutional leaders, managers, and experts. Data credibility is carried out through triangulation and transferability tests. The results of the study state that Human Capital plays a role in driving the performance of Islamic philanthropic institutions in the first 15 years, after which Structural Capital dominates the performance of the organization. The IC role model shows how this Islamic philanthropic institution empowers mustahiq to become muzakki and contribute to the SDGs, especially poverty alleviation and economic growth. Guided by The Human Capital Theory and The Institutional Theory, this study provides a framework for utilizing IC as a strategic asset for organizations. This study uniquely connects IC with Islamic philanthropy, introducing a new model to improve performance and drive sustainable development.